2017
DOI: 10.1590/0370-44672015700189
|View full text |Cite
|
Sign up to set email alerts
|

Study of the electricity consumption reduction of a compressed air system: the case of a steelmaking company

Abstract: This work aims to reduce the energy consumption and thus increase the availability of blast furnace compressors of a steelmaking company, located in Alto Paraopeba region in Minas Gerais state, Brazil, through the elimination of waste points in the compressed air distribution. In order to develop this work, an ultrasound test in the compressed air line was performed to identify and quantify leaks in the flow. Once the leaks were identified, they were eliminated through corrective maintenance and improvements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…In recent market research, the global compressor market was reported at USD 39.9 billion in 2019, and it is expected to reach USD 48.5 billion by 2030, with the majority of the market share contributed by positive displacement compressors [9]. It is worth mentioning that compressed gas is regarded as one of the most expensive energy forms [10]. It was reported that nearly 20% of energy consumption in industries is attributed to producing compressed gas [11], whereas less than 30% of the compressed gas can be efficiently used [12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent market research, the global compressor market was reported at USD 39.9 billion in 2019, and it is expected to reach USD 48.5 billion by 2030, with the majority of the market share contributed by positive displacement compressors [9]. It is worth mentioning that compressed gas is regarded as one of the most expensive energy forms [10]. It was reported that nearly 20% of energy consumption in industries is attributed to producing compressed gas [11], whereas less than 30% of the compressed gas can be efficiently used [12].…”
Section: Introductionmentioning
confidence: 99%